Sikap Profesional Pustakawan dalam Layanan Informasi - Quthbi Habibin, Firulla; Masruri, Anis (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study investigates the growing importance of librarian professionalism in the increasingly complex landscape of digital information services. Although discussions about technical competence have expanded in recent years, comprehensive studies that integrate both technical and ethical dimensions remain limited. Using a systematic literature review approach, this research examines key components of librarian professionalism, including technical skills, work ethics, communication abilities, integrity, transparency, and empathy. The findings reveal that professionalism affects not only the accuracy, reliability, and efficiency of information services but also significantly shapes user trust, comfort, and overall service satisfaction. Ethical values and strong interpersonal communication emerge as indispensable elements that enhance service quality, complementing technical proficiency in digital environments. The novelty of this study lies in its integrative analytical framework, which brings together technical and ethical aspects into a unified perspective for understanding librarianship professionalism. The study provides a conceptual foundation for developing institutional policies, competency-based training, and professional work cultures in libraries. Ultimately, it highlights the need for adaptive, credible, and human-centered information services as libraries navigate the challenges of the digital era.